2021
DOI: 10.3390/ijerph182413032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spousal Loss on Depression in Older Adults: Impacts of Time Passing, Living Arrangement, and Spouse’s Health Status before Death

Abstract: In addition to increasing the mortality among older adults, spousal death (SD) increases their risk of depression. This study explored the factors affecting depression among widowed older adults to provide health care strategies for successful aging. A total of 710 adults older than 60 years completed a questionnaire before and after their spouses’ deaths. The survey data included age, sex, ethnic group, education level, financial station socioeconomic status, SD (including time point), smoking status, alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…In this study, elevated levels of depression were notably observed among widowed elderly patients, a finding consistent with research by Hung et al [ 25 ] .This underscores the potential impact of having family support nearby on increased social interactions and enhanced self-esteem. Additionally, a lower prevalence of depression was noted among patients with a university education or higher, as indicated by Keyes et al [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, elevated levels of depression were notably observed among widowed elderly patients, a finding consistent with research by Hung et al [ 25 ] .This underscores the potential impact of having family support nearby on increased social interactions and enhanced self-esteem. Additionally, a lower prevalence of depression was noted among patients with a university education or higher, as indicated by Keyes et al [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…Many previous studies have also found a positive correlation between depression and worsened mobility in elderly. 21,22 As disability and mobility problems increase with age, use of assistive devices such as canes, crutches, and walkers, increase a patient's base of support, improves balance, increased activity and independence, proving that significant association between functional dependency in ADL and assistive device use among the elderly may exist, as found in our study.…”
Section: Discussionsupporting
confidence: 63%
“…Some studies found that living alone was a risk factor for depression in older adults, while others found no association. There was also some evidence to suggest that the relationship between living arrangement and depression may vary by gender ( 26 ). Additionally, the relationship between living arrangement and depression may be influenced by other social factors, such as social support, social isolation, and life events.…”
Section: Discussionmentioning
confidence: 99%